Understanding Illegal Cosmetic Circulation in Indonesian Online Marketplace through Problem Analysis Triangle - Edi Priyo Yunianto; Yudo Anggoro (AIBPM Publisher, 2021)
In Indonesia, selling cosmetic products that do not have a distribution permit is an unethical business practice and even a criminal act that violates regulations that require every cosmetic must have a distribution permit and meet safety and quality standards. This business practice certainly can threaten the Indonesian cosmetic business climate and threaten Indonesian cosmetic consumers with both economic and health consequences. This study aims to identify the factors causing illegal cosmetic circulation in the Indonesian online marketplace. Collected data from consumer surveys, observation, and interviews, were analyzed by the problem analysis triangle. The result shows that seven factors are causing illegal cosmetic circulation in the Indonesian online marketplace: consumer's lack of awareness on cosmetic legality; difficulty in identifying the legality of cosmetic products; seller's opportunity to sell illegal cosmetic products; seller's motive; seller's lack awareness on cosmetic legality; lack of supervision in the marketplace; and less controlled environment. The result of the study can be used as a basis for the Indonesian FDA to develop a comprehensive prevention strategy.